The combustion and emission characteristics of a common-rail diesel engine fueled with diesel and higher alcohols blends with a high blend ratio. (15th December 2022) - Zhao, Weihua; Yan, Junhao; Gao, Suya; Lee, Timothy H.; Li, Xiangrong
Abstract: Experiments were conducted to investigate the effects of different alcohol additives on the combustion and emission characteristics of a diesel engine. Diesel was blended with four higher alcohols (propanol, butanol, pentanol, and hexanol) with a blend ratio of 40% by volume. To evaluate the engine performance at different engine loads, four loads ranging from 0.35 to 0.65 MPa IMEP (Indicated mean effective pressure) were conducted. Diesel/higher alcohol blends showed longer ignition delays and shorter combustion durations in comparison to diesel. Diesel had lower indicated specific fuel consumption (ISFC) values compared to diesel/alcohol blends. At the engine load of 0.35 MPa IMEP, Pr40 (40% propanol + 60% diesel) and Pe40 (40% pentanol + 60% diesel) had higher indicated thermal efficiency (ITE) than that of diesel. When the engine load increased to 0.45 MPa IMEP, Pe40 still had a larger ITE than diesel. Pe40 showed the highest ITE among the diesel/alcohol blends at different engine loads. The emission results showed that diesel/higher alcohol blends had higher NOx (oxides of nitrogen) and lower soot emissions than that of diesel under all test conditions. Overall, Pe40 and H40 (40% hexanol + 60% diesel) were good alternative fuel blends for diesel engines at high loads with only a slight trade off in combustion efficiency and NOx emissions. Highlights: Diesel/higher alcohol blends with a high blend ratio were investigated. Propanol, butanol, pentanol and hexanol were as fuel blends in this work. Pdae40 had the highest ITE among the diesel/alcohol blends at different engine loads. Pe40 and H40 were good alternative fuel blends for diesel engines at high loads.